Three new species of Penicillidmus in the Philippines (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2019)
Until now, Penicillidmus was represented by two Australian and one Papuan species, distributed in Cape York, northern Queensland, and Lavongai Island, Papua New Guinea. Three new species are described, all known to occur in Luzon, the Philippines: Penicillidmus maquilingensis sp. n., P. lagunensis sp. n. and P. luzonicus sp. n. The discovery of Penicillidmus in the Oriental region suggests a broader distribution of this genus in Southeast Asia.